Multimodal Communication Strategy in Language Teaching for Generation Z - Hamid, Abdul (Journal of English Language and Education, 2025)
The development of digital technology demands a change in communication strategies in language teaching, especially for Generation Z who have a preference for visual and interactive approaches. This study aims to describe the multimodal communication strategies applied in language learning, their effectiveness, and the challenges faced. The method used is Systematic Literature Review with an analysis of relevant studies based on open access over the past ten years. The findings of this study show that multimodal communication increases student engagement and understanding, but has not been widely optimized by educators.  This research emphasizes the urgency of multimodal integration in language teaching and the need for teacher training and digital-based curriculum development to answer the needs of the digital-native generation. In addition, this research makes a theoretical and practical contribution to the reform of language education today.